Hidden educational inequalities in high blood pressure and high blood glucose levels in Kerala: evidence from the National Family Health Survey (2019–2021) - Devaki Nambiar; Santosh Kumar Sharma; Jaison Joseph (BMJ Open)
Objective This study assesses educational inequalities in measured as well as self-reported high blood pressure (BP) and high blood glucose (BG) in the southern Indian state of Kerala, which is known to have high chronic disease morbidity.Design The present findings are drawn from a large-scale, nationally representative cross-sectional study.Settings and participants India’s Demographic and Health Survey (conducted in 2019–2021) had data on 36 526 individuals aged 15 years and above in the state of Kerala, India.Primary and secondary outcomes measures Measured high BP and BG; self-reported high BP and BG; as well as self-reported BP and BG testing. Descriptive statistics, bivariate analysis, along with multivariate statistics, were used. Educational inequalities were assessed through absolute and relative complex measures of inequality, namely the Slope Index of Inequality (SII) and Relative Concentration Index (RCI), respectively, with 95% CIs.Results The largest margin of inequality in Kerala, between the least and the most educated groups, was observed for measured high BP (57.7% and 17.6%). Measured high BP (SII −45.4% (95% CI –47.3% to –43.4%); RCI −26.6% (95% CI –27.9% to –25.3%)), self-reported high BP (SII −34.5% (95% CI –36.3% to –32.7%); RCI −19.0% (95% CI –20.1% to –17.9%)). High BG levels were concentrated among those with lower educational attainment (SII −26.6% (95% CI –28.6% to –24.7%); RCI −15.7% (95% CI –16.9% to –14.5%)), represented by negative SII and RCI values.Conclusions The study findings suggest that research and programme efforts need to be redoubled to determine what is driving greater vulnerability to non-communicable diseases among population with lower educational attainment on the one hand and the possible role that improving education access can be on health outcomes, on the other hand. Further research should explore relevant intersections with low education.